Kedudukan Alat Bukti Digital Dalam Pembuktian Cyber Crime Di Pengadilan - Handoko, Cahyo; , Dr. Natangsa Surbakti, S.H., M.Hum; , Marisa Kurnianingsih, S.H, M.H, M.Kn (2015)
Basically every law made by the makers of the Act is the answer to the question of public law at the time of the creation of such laws. Along with the development needs of the people in the world, information technology plays an important role, both in the present and in the future. Information Technology by itself is also changing people's behavior to perform an unlawful act. Tort is called cyber crime. This study uses empirical juridical pendekata, descriptive. Using these types of primary and secondary data. Data collection technique is done by through library research and interviews. By using qualitative data analysis.It can be concluded that the system of proof and evidence based on Article 184 of the Criminal Procedure Code was able to reach proof of cyber crime crime classified as a new criminal offense. Search for evidence such as witness testimony conventional, and expert witnesses, as well as a shift from conventional letters and instructions to the electronic, digital evidence in this position to influence the course of evidence and the judge's decision. Article 5 paragraph (1) Act No. 11 of 2008 on Information and Electronic Transactions states that "Electronic information is a valid legal evidence